Study prevalence of peripheral arterial disease in diabetics with coronary artery disease at a large tertiary care teaching hospital in North India - Bhat, Sajad Hussain; Dar, Mohd Yousuf; Majeed, Aadil (International Journal of Research in Medical Sciences, 2020)
Background: Peripheral arterial disease and coronary artery disease have similar factors. The extent and severity of PAD is significantly associated with presence and severity of CAD. Methods: Patients were interviewed and clinical profile of patients including risk factors of coronary artery disease like diabetes, hypertension, smoking, dyslipidemia, obesity and family history of coronary artery disease were assessed and recorded in the proforma. Information regarding demographics, co morbidity, past history and family history was collected. Physical examination of each patient was carried and basic anthropometric data: height, weight, BMI and blood pressure, peripheral pulses calculated. Investigations both non- invasive and invasive including peripheral angiography were recorded. Results: In this prospective study fifty (50) type 2 diabetes patients admitted with CAD were studied whose mean age was 55.6+8.2 and mean duration of diabetes was 6.8+8.4. In this study none of the patients with PAD had single atherosclerosis risk factors including diabetes. 30% patients were having two risk factors. PAD in in patients with CAD is particularly enhanced by the concomitant occurrence of two or more of these risk factors (p=0.016). Hypertension as a predictor of PAD was statistically significant (p=0.0037). In this study the duration of diabetes was <5 years in 10%, 5-10 years in 40% and >10 years in 40% of patients with angiographically proven PAD. Conclusions: It was observed that presence and severity CAD was significantly associated with PAD.